QUATERNARY STRATIGRAPHY AND SOIL DEVELOPMENT AT THE SOUTHERN BORDER OF THE CENTRAL ALPS (ITALY): THE BAGAGGERA SEQUENCE (Rivista italiana di Paleontologia e Stratigrafia, 2020)
A complcx sequence exposed in clay Pit, near Bagaggera, is described in some details. Palaeomagnetic stratigraphy and archaeologic fillds indicate that the sediments of the Bagaggera basin accumulated at least from Farly Pleistocene up to Late Pleistocene. The sedimentary development, reconstructed on the ground of sedimentary, petrographic and mineralogical evidences, has been determined by climatic variations and tectonic activity. Five glacial Stages are recorded in thesedimentary sequence, the oldest one dating back to Early Pleistocene, and only the' last two are directly connected with the front of the Alpine glaciers.Five different paleosols are interlayered in the basin fill; they indicate that, during Interglacial periods of Middle and part of Early Pleistocene, soil forming processes were not very different from those which operated in Postglacial times. On the contrary the oldest paleosol, dating back to Early Pleistocene or Late Pliocene, is due to stronger weathering and probably developed in a different pedoclimatic environment. Further the stratigraphic and genetic meaning of some soil features, very frequent in Lombard paleosols, is discussed.